2022
DOI: 10.3389/fcvm.2022.823076
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Pro-B-Type Natriuretic Peptide in Risk Stratification of Heart Failure Patients With Implantable Cardioverter-Defibrillator

Abstract: BackgroundThe prognostic value of N-terminal pro-B-type natriuretic peptide (NT-proBNP) in heart failure (HF) is well-established. However, whether it could facilitate the risk stratification of HF patients with implantable cardioverter-defibrillator (ICD) is still unclear.ObjectiveTo determine the associations between baseline NT-proBNP and outcomes of all-cause mortality and first appropriate shock due to sustained ventricular tachycardia/ventricular fibrillation (VT/VF) in ICD recipients.Methods and results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Conclusively, after detailed consideration, nine studies were chosen for final inclusion, with a total of 5117 participants incorporated in this meta-analysis (figure 1). 11–18 26 The participant in this research had a mean age of 62.4 years, whereas 76.4% of the participants were men. Amid the overall patients, the aetiology of 48.5% patients was ischaemic and the mean duration of follow-up was 3.6 years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Conclusively, after detailed consideration, nine studies were chosen for final inclusion, with a total of 5117 participants incorporated in this meta-analysis (figure 1). 11–18 26 The participant in this research had a mean age of 62.4 years, whereas 76.4% of the participants were men. Amid the overall patients, the aetiology of 48.5% patients was ischaemic and the mean duration of follow-up was 3.6 years.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with HF with ICD, greater NT-pro BNP levels were generally linked with all-cause mortality (HR=2.12 (95% CI=1.53 to 2.93); p<0.001), but with considerable heterogeneity (I 2 =78.1%, p<0.001 for heterogeneity) (figure 2A). Succeeding a leave-one-out analysis, however, revealed that two studies14 15 markedly increased heterogeneity within the included studies. Following the withdrawal of the aforementioned studies, heterogeneity fell substantially (I 2 =0%, p=0.587 for heterogeneity), and the pooled effect size remained statistically significant (HR=1.57 (95% CI=1.40 to 1.76); p<0.001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations